PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN FLASHCARD DIGITAL TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS IV SD - Sastri Nurdila; Muhsana El Cintami Lanos; Ida Suryani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine whether there is an influence of using digital flashcard learning media on students' learning interest in the IPAS subject for Grade IV elementary school students. This research is a quantitative study using a quasi-experimental method with a Nonequivalent Posttest-Only Control Group Design. The population in this study consisted of all fourth-grade students at SD Negeri 92 Palembang. The sample included students from classes IV.a and IV.b, totaling 40 students. The sampling technique used was saturated sampling. Data collection techniques included questionnaires and documentation. Data analysis was carried out using an Independent Samples T-test. The results showed that the average learning interest questionnaire score was 88.05 for the experimental class and 67.75 for the control class. The t-test results for learning interest showed a t-value of 28.215 ≥ t-table of 1.686 at a significance level of 0.05. Based on the analysis, it can be concluded that the use of digital flashcard learning media has a significant effect on students' learning interest in the IPAS subject for Grade IV elementary school students.